2010
DOI: 10.1007/s11270-010-0707-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pyrene Adsorption on Two Brazilian Soils

Abstract: This study investigated pyrene adsorption on two contrasting Brazilian soils: a Kandiudult and a Vertisol. It was found that the time taken to reach thermodynamic equilibrium depended on the soil type. The curves for different pyrene-to-soil mass ratios for Vertisol soil showed significant differences. This is probably related to the presence of 2:1 clays that may increase the adsorption of pyrene due to the resulting interlamellar space. The adsorption of pyrene on the Kandiudult showed, in general, good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…This trend was attributed to the fact that when the transport of metals between the sorbent's external surface film and internal pores are equal, the trans-boundary movement of metals will not be significantly permissible; however, increasing concentration will re-initiate the trans-boundary movement and hence, the process will be concentration dependent. Similar findings have been reported in literature for similar and other pollutants adsorption [1,38,39]. The Figures also showed that increase in temperature did not lead to any significant increase in adsorption except for Cu(II) on the BEN clay.…”
Section: Equilibrium Experiments and Effect Of Temperaturesupporting
confidence: 90%
“…This trend was attributed to the fact that when the transport of metals between the sorbent's external surface film and internal pores are equal, the trans-boundary movement of metals will not be significantly permissible; however, increasing concentration will re-initiate the trans-boundary movement and hence, the process will be concentration dependent. Similar findings have been reported in literature for similar and other pollutants adsorption [1,38,39]. The Figures also showed that increase in temperature did not lead to any significant increase in adsorption except for Cu(II) on the BEN clay.…”
Section: Equilibrium Experiments and Effect Of Temperaturesupporting
confidence: 90%
“…Their effect on biota can be amplified by bioaccumulation in the food chain because PAHs like most organic pollutants are very soluble in fat. Once in the environment, they are subjected to various physical and/or chemical processes that determine their environmental fate (Okoli et al, 2014;Teixeira et al, 2011;Ramirez et al, 2001). Information on the bioavailability of pollutants in the environment is important because bioavailable pollutants are linked to the negative health disorders experienced by biota.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various processes that determine the environmental fate of PAHs, sorption is the relatively most studied (Teixeira et al, 2011;Ramirez et al, 2001) because data obtained can give valuable information on suitable remediation strategy for the polluted soil. Sorption experiments can be used to determine the quantity of PAHs retained by a soil and, hence, the leachable or bioavailable quantity (Sparks, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As this soil's organic matter content is below 0.1%, pyrene sorption was attributed to fine soil materials (Karichoff 1984). As Gonen and Rytwo (2006) reported, clays are not normally characterized as adsorption sites for PAHs; however, with the expansion of the interlamellar space caused by the hydratation of the clays, more sorption sites appear to become available (Teixeira et al 2010). …”
Section: Resultsmentioning
confidence: 86%
“…When organic matter content is below 0.1%, sorption and desorption processes are attributed to fine soil materials, mainly clays (Karichoff 1984;Teixeira et al 2010). Granulometry is strongly connected with the cation exchange capacity (CEC), which affects the achievement of CMC eff (Jönsonn et al 1998;Mulligan et al 2001).…”
mentioning
confidence: 99%